The German Federal Network Agency - Silva, Patrick Leonardo de Faria e (Law, State and Telecommunications Review, 2009)
The purpose of this paper is to analyze the Federal Network Agency (Bundesnetzagentur), the new name for the Regulatory Authority for Telecommunications and Posts (RegTP) in the Federal Republic of Germany. In the first part of the article will be described the historical evolution of the telecommunication’s Law in Germany. The second part is devoted to explaining the reasons for the creation of the Bundesnetzagentur, its tasks and its organization.